Combining systemic and pragmatic approaches for the holistic diagnosis of a farm in agroecological transition in a health context - Cremilleux, Maeva; Michaud, Audrey; Cayre, Patrice; Martin, Bruno; Rigolot, Cyrille; Michelin, Yves (Frontiers in Sustainable Food Systems, 2023)
Today, agriculture and livestock farming are facing environmental, social and health challenges. The agroecological transition is a possible response to these challenges. It requires changes in practices but also an evolution in farmers' ways of thinking and relationships with living things. Some diagnostics of farms, such as the global analysis of farms, are not sufficient to analyse systems in the face of the agroecological transition. They do not capture many nuances of farmers’ values, behaviors and practices. We therefore propose a holistic approach combining a global analysis of farms and a pragmatic approach to understand the functioning of agricultural production systems. This pragmatic turn enables to integrate the ways in which the farmer's reality is established, the performance of the system, the associated metrics and the farmer's relationship with life. Using the example of a farm in transition, we show that it is the combination of pragmatism and a systemic approach, within an interview, which makes it possible to understand farms and their coherence. The proposed methodology requires a change in the researcher’s stance and allows for a renewed dialogue between research and farmers in the field.